Pengaruh Penggunaan Media Pembelajaran Interaktif Terhadap Pemahaman Konsep Matematika Siswa - Nurul Aisyah; Misnah Sakinah Psb; Sofiyah, Khotna (INDO PUBLISHING, 2025)
The purpose of this study was to analyze the effect of using interactive learning media on students’ understanding of mathematical concepts. This study compiles literature that includes various studies examining the relationship between the use of interactive media, such as educational software, web-based applications, and visual aids, with improving students’ understanding of mathematical concepts at various levels of education. The methodology used in this study is a descriptive analysis of relevant academic journals, including meta-analysis and thematic synthesis of previous research results. The results of the study indicate that the use of interactive learning media significantly improves students’ understanding of mathematical concepts through increased motivation, active involvement, and opportunities for collaborative learning. In addition, interactive media provides faster and more relevant feedback, which helps students understand the material better. This study concludes that the integration of interactive learning media in mathematics teaching can be an effective strategy to improve students’ understanding of complex mathematical concepts.